MATERIALISME DIALEKTIS DALAM RUANG MAYA DITINJAU DARI PERSPEKTIF KARL MARX SEBAGAI UPAYA MEMBANGUN TEOLOGI KEKINIAN - Henri Sirangki; Yefta Noval (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2025)
The purpose of this study is to educate church members/society who have been hypnotized and even exploited by technology. They forget that, in order to access te internet, they have to spend money, because it can make us decline (financially) due to internet addiction. Meanwhile, the owners of platfroms, for example, are getting richer (capitalists). The research method used is qualitative, literature review approach by examining books/journals that are coherent whit the topic, especially axamining Karl Marx’s perspective regarding dialectical materialism, to find its coherence ini cyberspace. The results to the study show that the digital word (cyberspace) was born because of material, from this material gave birth to new technologies which in turn produced more material. Therefore, there is a dialectical materialism in cyberspace, for example users create content with capital (material) that expects more material, unaware that the only beneficiaries are paltfrom owners (capitalists). In building contemporary theology as a response to the development of dialectical materialism in cyberspace, the author offers three things: first, a contextual theology approach. By contextualizing theological teachings, it can answer the problems of digital capitalism. Second, a liberation theology approach, which provides a perspective so that those exploited by the world of digital capitalism can be free. Third, the development of digital postcolonial theology. This is done as an effort to break down global capitalism in digital space, so that the curch community is free from the shadows of digital imperialism.